Correlation between temporomandibular joint dysfunction and Eichner classification - Krzewski, Szymon; Baranowski, Mateusz; Zubrzycki, Robert; Stachurski, Maciej; Borowicz, Janusz (Journal of Education, Health and Sport, 2020)
Introduction: The Dental Prosthetics Department’s most common patients are elderly who have lost their teeth. Dental deficiencies not only impair the functions of the stomatognathic system but can also be the cause of temporomandibular disorders (TMD). Deficiencies in the lateral sections lead to a decrease in the occlusion height in patients, which negatively affects the aesthetics of the face by shortening the lower floor and overloading the remaining teeth, eventually leading to their pathological wear. Loss of occlusion height changes the spatial arrangement of the lower jaw to the upper jaw, which can lead to changes in the temporomandibular joint. The loss of a tooth or group of teeth is an indication for proper prosthetic treatment. The dentist should be able to take into account, evaluate and, if necessary, cure TMD, but this is not a common skill among dentists. Such treatment requires an appropriate comprehensive approach. There are currently no standards for such treatment. We presented one of the methods as part of our study. Purpose of work: The aim of the study was to check the correlation between the occurrence of temporomandibular disorders and missing teeth and used prosthetic restorations. Material and methods: Medical history records of 58 patients under the care of the Department of Dental Prosthetics at Medical University of Lublin were analyzed. Factors such as age and gender, occlusion height, distribution of missing teeth according to the Eichner classification and symptoms of temporomandibular joint disorders, i.e. crackling, pain, limited and excessive abduction of the jaw were checked. Before starting prosthetic treatment, every patient underwent comprehensive conservative, surgical and periodontics treatment in accordance with existing needs. Results: The study group consisted of 38 women and 20 men. The average age of all patients was 69.6 years; - average for men - 70.45 years, women 68.16 years. The oldest patient was an 88-year-old man, and the youngest was a 43-year-old woman. 31% of patients were toothless. 25.9% of patients had pain within the stomatognathic system, of which 86.7% were women and 13.3% men. Relaxation splint was made in 24.1% of patients. Summary: The study showed that the ailments associated with the stomatognathic system are correlated with a reduction in occlusion height. Larger dental deficits are more common in older people. Pain symptoms are the most common cause of making relaxation splints. Women more often than men complain of pain. The correct treatment scheme for patients with missing teeth and long-term loss of support zones is staggered treatment - two-stage. The first stage of treatment is to restore the correct occlusion height by using the occlusal splint. Then, after the adaptation period, there is a transition to the second stage of treatment - the use of proper prosthetic restoration maintaining the correct height of occlusion